2007
DOI: 10.1371/journal.pone.0000364
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Stress-Induced Learning Impairment and Associated Brain Gene Expression from Parents to Offspring in Chickens

Abstract: BackgroundStress influences many aspects of animal behaviour and is a major factor driving populations to adapt to changing living conditions, such as during domestication. Stress can affect offspring through non-genetic mechanisms, but recent research indicates that inherited epigenetic modifications of the genome could possibly also be involved.Methodology/Principal FindingsRed junglefowl (RJF, ancestors of modern chickens) and domesticated White Leghorn (WL) chickens were raised in a stressful environment (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
91
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 17 publications
11
91
0
1
Order By: Relevance
“…We also excluded a similar case in mice which showed that tumor risk was increased following chromium III chloride exposure and that this risk was then transmitted from father to son (Shiao et al 2005). Other cases of single-generation inheritance, such as protection against type I diabetes in humans (where a paramutation-like process has been reported) (Bennett et al 1997), hydrostatic pressure-induced alterations in DNA methylation in Japonica rice (Long et al 2006), and parallel alterations in gene expression profiles in White Leghorn chickens and their offspring following stress in the parental generation (Lindqvist et al 2007), were also excluded, although epigenetic inheritance may well have occurred and may be revealed when subsequent generations are studied. However, within the limitations imposed by the research designs of the studies we reviewed and the qualifications we have mentioned, we believe that the table provides a fairly exhaustive overview of the recognized cases of cellular transgenerational epigenetic inheritance that have been described in English-language journals, although, inevitably, we likely missed some cases.…”
Section: Cases Included In the Tablementioning
confidence: 99%
“…We also excluded a similar case in mice which showed that tumor risk was increased following chromium III chloride exposure and that this risk was then transmitted from father to son (Shiao et al 2005). Other cases of single-generation inheritance, such as protection against type I diabetes in humans (where a paramutation-like process has been reported) (Bennett et al 1997), hydrostatic pressure-induced alterations in DNA methylation in Japonica rice (Long et al 2006), and parallel alterations in gene expression profiles in White Leghorn chickens and their offspring following stress in the parental generation (Lindqvist et al 2007), were also excluded, although epigenetic inheritance may well have occurred and may be revealed when subsequent generations are studied. However, within the limitations imposed by the research designs of the studies we reviewed and the qualifications we have mentioned, we believe that the table provides a fairly exhaustive overview of the recognized cases of cellular transgenerational epigenetic inheritance that have been described in English-language journals, although, inevitably, we likely missed some cases.…”
Section: Cases Included In the Tablementioning
confidence: 99%
“…Although seldom sought, these have been documented in diverse taxa (Burton and Metcalfe 2014), including 4 species of birds. Application of experimental stresses to captive nestlings or juveniles induced deficits in their offspring: diminished size, hatching success, and nest success in female Zebra Finches (Naguib and Gil 2005, Naguib et al 2006, Alonso-Alvarez et al 2007); reduced spatial learning or corticosterone responsiveness in breeds of Domestic Fowl (Lindqvist et al 2007, Goerlich et al 2012; and increased fearfulness in Japanese Quail (Guibert et al 2012). In nature, however, intergenerational effects are unlikely to be just a matter of imposed deficits and, on present evidence, sometimes reflect adaptive plasticity.…”
Section: Discussionmentioning
confidence: 68%
“…In nature, however, intergenerational effects are unlikely to be just a matter of imposed deficits and, on present evidence, sometimes reflect adaptive plasticity. A hint of such potential comes from the offspring of white leghorn chicks exposed to unpredictable light-dark rhythms (Lindqvist et al 2007) which, despite their poor spatial learning, were more competitive and grew faster than controls. More persuasive, perhaps, are the 2 intergenerational effects so far observed in free-living birds that can be interpreted as strategic deferral of costs or compensatory adjustment for them.…”
Section: Discussionmentioning
confidence: 99%
“…A corresponding transgenerational effect of early maternal separation has also been found in female mice (Weiss, Franklin, & Vizi, 2011). My group has demonstrated transgenerational, epigenetically mediated changes in behaviour in chickens as a result of both chronic stress (Lindqvist et al, 2007) and brief events of early social isolation (Goerlich, Nätt, Elfwing, Macdonald, & Jensen, 2012). Also "positive" experiences may transmit across generations.…”
Section: Transgenerational Effects and Inheritance Of Epigenetic Modimentioning
confidence: 91%
“…Most of the studies referred to here have not examined the possible epigenetic mechanisms involved, even though it appears evident that such mechanisms must play an important role. For example, although the exact mechanisms are unknown, my group has shown that stress induced modifications in hypothalamic gene expression profiles are significantly mirrored in the offspring of the affected animals (Goerlich et al, 2012;Lindqvist et al, 2007;Nätt et al, 2009). …”
Section: Stress As a Mediator Of Epigenetic Effectsmentioning
confidence: 99%